Antibiogram & Multidrug Resistance among Bacteria Isolated from Pigs with Respiratory Illness in Western Uttar Pradesh - Chaudhary, Sachin; Katoch, Shailja; Chandra, Naresh; Jaiswal, Vikas; Bhatele, Aarti; Singh, Rajeev (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was undertaken to identify the bacteria causing respiratory illness in pigs of western Uttar Pradesh, their antibiogram and multi-drug resistance. Fifty nasal samples were collected from pigs exhibiting respiratory clinical signs using sterile swabs. The samples were processed for isolation and identification of bacteria by conventional bacteriological methods. Forty-six bacteria were isolated, out of which 76.08% (35/46) were Gram negative and 23.91% (11/46) were Gram positive. Eight bacteria, viz., Escherichia coli (15.21%), Pasteurella multocida (15.21%), Proteus vulgaris (13.04%), Bordetella bronchiseptica (13.04%), Pseudomonas aeruginosa (13.04%), Streptococcus suis (10.86%), Staphylococcus aureus (10.86%) and Klebsiella pneumonia (8.69%) were identified. The in-vitro antibiotic sensitivity test of the bacterial isolates revealed, enrofloxacin and amikacin (78.26% each) as the most effective antibiotics followed by tetracycline, gentamicin, colistin (76.09% each) and streptomycin (67.39%). Among the bacterial isolates, highest resistance was found against amoxyclav (58.70%) followed by ampicillin (54.35%), chloramphenicol (47.83%) and cefixime (45.65%). In the present study, 31(67.39%) isolates out of 46 showed multi-drug resistance (MDR). 34 (73.9%) bacterial isolates had multiple antibiotic resistance index (MARI) greater than 0.2. The study revealed that E. coli, P. multocida, P. vulgaris, B. bronchiseptica, P. aeruginosa, S. suis, S. aureus and K. pneumonia are the common bacteria that lead to respiratory diseases in pigs of western UP. The increased incidence of MDR isolates and MARI of > 0.2 emphasizes the significance of employing antimicrobials judiciously at the farms.
Keywords: Antibiogram; Bacterial isolates; MARI; MDR; Pig; Respiratory Illness